Physiological testing of basketball players: Toward a standard evaluation of anaerobic fitness - Delextrat, A.; Cohen, D. (The Journal of Strength and Conditioning Research, 2008)
The aim of this study was to examine whether the changes in the rules of the game instituted in 2000 have modified the physiological factors of success in basketball. The performances of 8 elite male players and 8 average-level players were compared in order to identify which components of fitness among agility, speed, anaerobic power, anaerobic capacity, and upper body strength were key determinants of performance in modern basketball. Each subject performed 7 tests, including vertical jump (VJ), 20-m sprint, agility T test, suicide sprint, 30-second Wingate anaerobic test (WAnT), isokinetic testing of the knee extensors, and 1 repetition maximum (1RM) bench press test. The statistical difference in the anaerobic performances was assessed by Student's t test. The main results showed that, compared to average-level players, elite-level players achieved significantly better performances in the agility T test (+6.2%), VJ test (+8.8%), peak torques developed by knee extensors (+20.2%), and 1RM bench press (+18.6%, p < 0.05). In contrast, no significant difference between groups was observed on 20-m sprint, suicide run, and parameters of the WAnT (p > 0.05). These results emphasized the importance of anaerobic power in modern basketball, whereas anaerobic capacity does not seem to be a key aspect to consider. In this context, coaches are advised to avoid using exercises lasting >=30 seconds in their physical fitness programs, but instead to focus on short and intense tests such as VJ, agility T test, and sprints over very short distances (5 or 10 m).